Personal reboot and survival - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
The article contains a reconstruction of the rapid psychological change argument by Scott Campbell. According to the standard psychological approach, the identity of a person is tied to persistence one’s memories, beliefs, wants and intentions. A person stays the same person if one holds strongly psychologically connected and continuous over time. The structure of rapid psychological change argument is compared with the argument of incredibly long-lasting psychological change by David Lewis. It is concluded that the main goals of critical attacks of these arguments are the temporal mismatch of psychological connectedness and continuity as well as the reductionist claim that all the facts what matters for survival can be described in an impersonal way